Kontribusi Daya Ledak Otot Tungkai dan Kekuatan Otot Tengan Terhadap Open Smash Bola Voli Siswa SMP Negeri 6 Kotabaru - Jusran S (STKIP Paris Barantai, 2019)
This research is a type of descriptive research. This study aims to determine: (1) whether there is a contribution of explosive muscle leg power to the volleyball smash ability of Kotabaru 6 Public Middle School students. (2) whether there is a contribution of arm muscle strength to the volleyball smash ability of Kotabaru 6 Public Middle School students. (3) is there a contribution of explosive muscle leg power and arm muscle strength to the volleyball smash ability of Kotabaru 6 Public Middle School students.The population is Kotabaru 6th Middle School Students. The sample used was 40 male junior high school students at Kotabaru State Middle School. The sample determination technique is by random selection by means of a simple random sampling. The data analysis technique used is descriptive analysis and inferential analysis through the SPSS 20 program at a significance level of Î± 0.05.The results of the study indicate that; (1) there is a contribution of explosive limb muscle power to the volley smash ability of Kotabaru 6 Public Middle School students, amounting to 22.4%, (2) there is a contribution of arm muscle strength to the volleyball smash ability of Kotabaru Public Middle School students at 22.5%, ( 3) there was a significant contribution together with explosive limb muscle strength and arm muscle strength on the volley smash ability of students of SMP Negeri 6 Kotabaru, amounting to 32.3% with F: 8.832 and sig (p) = 0.001. Keywords: Leg muscle explosive power, arm muscle strength, volleyball smash